Validation of in-cylinder flow of a controlled auto-ignition engine. (1st August 2014) - Beauquel, J.; Ibrahim, S.; Chen, R.
Abstract : Numerical calculations have been carried out to investigate the in-cylinder transient flow structure of a controlled auto-ignition (CAI) engine running at speeds of 1500 rpm and 2000 rpm. The calculated turbulent flow structure and velocities are validated against published laser doppler anemometry (LDA) experimental data (Pitcher et al., 2003). The experimental data was reprocessed to represent the time dependent mean velocities for all measured points. The actual geometry configuration of the engine is imported into the computational fluid dynamics (CFD) code used in this study. The simulations take into account the movement of the inlet, exhaust valves and the piston. The CFD simulations replicate the experimental work where only air was inserted into a driven optical engine. Also, to simulate an engine in controlled auto-ignition (CAI) mode, the same valve timing that allows 36% internal exhaust gas recirculation (IEGR) was applied for the air intake. The calculated results found to agree well with the LDA measurements with an overall agreement of 75.06% at 1500 rpm and 73.42% at 2000 rpm.